Sleeping-related distress in a palliative care population: A national, prospective, consecutive cohort. (October 2021) - Currow, David C; Davis, Walter; Connolly, Alanna; Krishnan, Anu; Wong, Aaron; Webster, Andrew; Barnes-Harris, Matilda MM; Daveson, Barb; Ekström, Magnus
Background: Sleep, a multi-dimensional experience, is essential for optimal physical and mental wellbeing. Poor sleep is associated with worse wellbeing but data are scarce from multi-site studies on sleeping-related distress in palliative care populations. Aim: To evaluate patient-reported distress related to sleep and explore key demographic and symptom distress related to pain, breathing or fatigue. Design: Australian national, consecutive cohort study with prospectively collected point-of-care data using symptoms from the Symptom Assessment Scale (SAS). Setting/Participants: People ( n = 118, 117; 475, 298 phases of care) who died while being seen by specialist palliative care services ( n = 152) 2013–2019. Settings: inpatient (direct care, consultative); community (outpatient clinics, home, residential aged care). Results: Moderate/severe levels of sleeping-related distress were reported in 11.9% of assessments, more frequently by males (12.7% vs 10.9% females); people aged <50 years (16.2% vs 11.5%); and people with cancer (12.3% vs 10.0% for other diagnoses). Sleeping-related distress peaked with mid-range Australia-modified Karnofsky Performance Status scores (40–60). Strong associations existed between pain-, breathing- and fatigue-related distress in people who identified moderate/severe sleeping-related distress, adjusted for age, sex and functional status. Those reporting moderate/severe sleeping-related distress were also more likely to experience severe pain-related distress (adjusted odds ratios [OR] 6.6; 95% confidence interval (CI) 6.3, 6.9); breathing-related distress (OR 6.2; 95% CI 5.8, 6.6); and fatigue-related distress (OR 10.4; 95% CI 9.99–10.8). Conclusions: This large, representative study of palliative care patients shows high prevalence of sleeping-related distress, with strong associations shown to distress from other symptoms including pain, breathlessness and fatigue.